A note on "price cap regulation of congested airports" - Christos Evangelinos; Antje Wittkowski; Ronny Püschel (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 2016)
Conventional economic models in airport regulation assume, that airports have considerable market power and may exploit it against airlines. Given, that many airports are served by only a limited number of airlines, mono- or oligopsony relationships may exist. This paper relaxes therefore this assumption. We use an existing model to test the impact of mono- and duopsony on the outcome of several regulatory options. Our results show, that in such cases the binding conditions for airport charges may change and, hence, optimal airport regulation should take into account also the degree of mono- or oligopsony airline power. In some cases the abolishment of any kind of regulation can lead to welfare gains.
Keywords: L51; L93; R41; 330; Airport Regulation; Single-Till; Dual-Till; Aitline Monopsony and Oligopsony Power